ANALISIS PENGETAHUAN PEREMPUAN TERHADAP PERILAKU MELAKUKAN PERNIKAHAN USIA DINI DI KECAMATAN WONOSARI KABUPATEN BONDOWOSO - Intan Arimurti; Ira Nurmala (The Indonesian Journal of Public Health, 2017)
One of the problems that still exist in Indonesia was e arly marriage. Early marriage was a marriage under years old 18 (UNICEF, 2014). Early marriage can be caused by many factors liked the k nowledge by women who do early age and her p arents. The purpose of this study was to analyze of k nowledge of women on the attitude of e arly marriage in Wonosari, Bondowoso District. This research was a descriptive research using qualitative approach, conducted in Wonosari, Bondowoso District. Researchers use a purposive way to determine the subject to be studied. Based on research results, low k nowledge of e arly marriage in women has a relationship with the low education of p arents, family, environment, mass media, experience about e arly marriage and the impact on health. Based on the results of the study could be concluded that the lower of  knowledge of women have higher attitude of tendency e arly marriage than higher k nowledge.